Prenatal diagnosis of maternal uniparental disomy 5 by amniocentesis associated with confined placental mosaicism for trisomy 5 and fetal trisomy 21 in a pregnancy - Chih-Ping Chen; Schu-Rern Chern; Liang-Kai Wang; Peih-Shan Wu; Fang-Tzu Wu; Yun-Yi Chen; Dai-Dyi Town; Chen-Wen Pan; Wayseen Wang (Elsevier, 2020)
Objective: We present prenatal diagnosis of maternal uniparental disomy (UPD) 5 by amniocentesis associated with confined placental mosaicism (CPM) for trisomy 5 and fetal trisomy 21 in a pregnancy. Case report: A 45-year-old woman underwent chorionic villus sampling (CVS) at 11 weeks of gestation because of maternal advanced age and an increased nuchal translucency of 4.0 mm in the first-trimester screening. CVS revealed a karyotype of 47,XY,+21[98]/48,XY,+5,+21[25]. Array comparative genomic hybridization (aCGH) analysis on the DNA extracted from chorionic villi revealed arr (5) × 3, arr (21) × 3 compatible with double trisomy 5 and trisomy 21. The woman underwent amniocenteses at 20 weeks and 22 weeks of gestation. Amniocenteses revealed a karyotype of 47,XY,+21. The parental karyotypes were normal. Quantitative fluorescent polymerase chain reaction (QF-PCR) on the DNA extracted from uncultured amniocytes showed trisomy 21 of maternal origin and maternal UPD 5. aCGH and interphase fluorescence in situ hybridization (FISH) on uncultured amniocytes confirmed trisomy 21. Prenatal ultrasound findings were unremarkable. The parents decided to continue the pregnancy, and a 2,198-g male baby was delivered at 38 weeks of gestation with characteristic phenotype of Down syndrome of hypertelorism, epicanthic folds and hypoplastic middle phalanx of the fifth fingers. Cytogenetic analysis of cord blood, umbilical cord and placenta revealed a karyotype of 47,XY,+21. QF-PCR analysis of the DNA extracted from placenta revealed double trisomy 5 and trisomy 21 with maternal gene dosage increase in chromosome 5 and chromosome 21. Conclusion: Prenatal diagnosis of CPM for trisomy 5 at CVS can be associated with UPD 5 in the fetus, and UPD 5 causes no specific phenotype.